Nanobody - Rothbauer, Ulrich; Chames, Patrick (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nanobodies have become outstanding tools for biomedical research, diagnostics and therapy. Recent advances in the identification and functionalization of target-specific nanobodies now make nanobody-based approaches broadly available to many researches in the field. This book provides a compilation of original research articles and comprehensive reviews covering important and up to date aspects of research on nanobodies and their applications for immunoassays, proteomics, protein crystallization and in vitro and in vivo imaging.